PENENTUAN KUALITAS FISIKA (WARNA, SUHU, DAN TDS) DARI SAMPEL AIR SUMUR WARGA DI KECAMATAN DUMAI TIMUR - Yelfira Sari; Arief Yandra Putra (UIR Press, 2019)
Water quality can be determined by doing certain test. Common parameter for determination water quality was physical, chemical, and biological parameter. This research was determined physical parameter, such as water colour, temperature, and TDS. Water colour determination was using eyesight sense while for temperature and TDS using a tool, thermometer for temperature determination and TDS-meter for TDS determination. Samples were taken from 5 Kelurahan in Dumai Timur District, that is Kelurahan Bukit Batrem, Kelurahan Buluh Kasap, Kelurahan Jaya Mukti, Kelurahan Tanjung Palas, and Kelurahan Teluk Binjai. Samples was taken from citizen wells which was selected in random as many as 2 samples for each Kelurahan. Water quality from samples was measured based on Regulation of Minister for Public Health No:416/MEN.KES/PER/IX/1990. Result of this research showed that all of water sample from Dumai Timur District were improper in physical parameter because of the water were turbid.